Chronic implantable flexible serpentine probe reveals impaired spatial coding of place cells in epilepsy - Wang, Yu; Han, Meiqi; Xu, Zhaojie; Lv, Shiya; Yang, Gucheng; Mo, Fan; Jing, Luyi; Jia, Qianli; Duan, Yiming; Xu, Wei; Jiao, Peiyao; Liu, Yaoyao; et al. (National science review, 2025)
The development of minimally invasive and reliable electrode probes for neural signal recording is crucial for advancing neuroscience and treating major brain disorders. Flexible neural probes offer superior long-term recording capabilities over traditional rigid probes. This study introduces a parylene-based serpentine electrode probe for stable, long-term neural monitoring. Inspired by the flexibility and morphology of snakes, the serpentine design of the probe ensures stable anchorage within the brain tissue during subject movement. The probe features a hydrophilic surface and is combined with a biodegradable silk fibroin–polyethylene glycol coating, significantly enhancing biocompatibility and mitigating inflammatory responses. In vivo experiments demonstrate that these probes enable stable, high-quality neural recordings for >8 months. The probes are also used to investigate the neural bases of epilepsy-induced cognitive deficits. By analysing place-cell dynamics in mice pre- and post-epileptic events, we identified the correlation between impaired spatial encoding and the observed cognitive deficits in epileptic mice. This study highlights the potential of our flexible probes in neurological research and medical applications.